Timing analysis of EXO 2030+375 during its 2021 giant outburst observed with Insight-HXMT. Issue 1 (27th February 2023) - Fu, Yu-Cong; Song, L M; Ding, G Q; Ge, M Y; Tuo, Y L; Zhang, S; Zhang, S N; Hou, X; Qu, J L; Zhang, J; Zhang, L; Bu, Q C; et al.
ABSTRACT: We report the evolution of the X-ray pulsations of EXO 2030+375 during its 2021 outburst using the observations from Insight -HXMT. Based on the accretion torque model, we study the correlation between the spin frequency derivatives and the luminosity. Pulsations can be detected in the energy band of 1–160 keV. The pulse profile evolves significantly with luminosity during the outburst, leading to that the whole outburst can be divided into several parts with different characteristics. The evolution of the pulse profile reveals the transition between the supercritical (fan-beam dominated) and the subcritical accretion (pencil-beam dominated) mode. From the accretion torque model and the critical luminosity model, based on a distance of 7.1 kpc, the inferred magnetic fields are (0.41 − 0.74) × 10 12 and (3.48 − 3.96) × 10 12 G, respectively, or based on a distance of 3.6 kpc, the estimated magnetic fields are (2.4 − 4.3) × 10 13 and (0.98 − 1.11) × 10 12 G, respectively. Two different sets of magnetic fields both support the presence of multipole magnetic fields of the neutron star.